Subclinical atherosclerosis in asymptomatic carriers of persistent antiphospholipid antibodies positivity: A cross-sectional study. (1st January 2019) - Di Minno, Matteo Nicola Dario; Emmi, Giacomo; Ambrosino, Pasquale; Scalera, Antonella; Tufano, Antonella; Cafaro, Giovanni; Peluso, Rosario; Bettiol, Alessandra; Di Scala, Gerardo; Silvestri, Elena; Prisco, Domenico
Abstract: Background: Whereas the relationship between subclinical atherosclerosis and antiphospholipid syndrome (APS) has been widely investigated, little is known about subclinical atherosclerosis in asymptomatic carriers with isolated antiphospholipid antibodies positivity (APP). Methods: Consecutive APP carriers, APS subjects and matched controls were enrolled. Intima-media thickness of the common carotid artery (CCA-IMT) and of the Bulb (Bulb-IMT) and the prevalence of carotid plaques were assessed in all enrolled subjects. Results: A total of 104 APP carriers, 221 APS subjects, and 325 matched controls were recruited. As compared with controls, APP carriers and APS subjects showed a higher CCA-IMT (0.90 ± 0.24 vs 0.82 ± 0.12, p = 0.014 and 0.93 ± 0.42 vs 0.82 ± 0.12, p < 0.001, respectively), Bulb-IMT (1.10 ± 0.44 vs 0.95 ± 0.18, p = 0.006 and 1.22 ± 0.68 vs 0.95 ± 0.18, p < 0.001, respectively) and an increased prevalence of carotid plaques (33.7% vs 10.2%, p < 0.001 and 38.5% vs 10.2%, p < 0.001, respectively). These results were confirmed stratifying for antibody isotype, after excluding subjects with systemic lupus erythematosus or other autoimmune diseases and after adjusting for major clinical and demographic variables. CCA-IMT, Bulb-IMT and the prevalence of carotid plaques were higher in subjects with high-titer antibodies and progressively increased for an increasing number of positive antibodies. Conclusions: Similar to APS subjects, APP carriers have enhanced subclinical atherosclerosis, a more severe disease being observed in the presence of high-titer antibodies and multiple antibodies positivity. These data argue for a strict monitoring of subclinical signs of atherosclerosis and of cardiovascular risk factors in asymptomatic APP carriers. Highlights: Carriers of antiphospholipid antibodies (APP) have enhanced carotid atherosclerosis. Carotid atherosclerosis is more severe in APP with high-titer antibodies. Carotid atherosclerosis is maximal in APP with multiple antibody positivity.